2009
DOI: 10.2967/jnumed.108.054205
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET and PET/CT in the Evaluation of Cancer Treatment Response

Abstract: Multimodality imaging, as represented by its greatest exponent, PET/CT, has a firm place in the evaluation of a patient presenting with cancer. With 18 F-FDG, PET/CT is rapidly becoming the key investigative tool for the staging and assessment of cancer recurrence. In the last 5 y, PET/CT has also gained widespread acceptance as a key tool used to demonstrate early response to intervention and therapy. In this setting, a major clinical need is being addressed with 18 F-FDG PET/CT, because of its inherent abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
176
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(183 citation statements)
references
References 71 publications
3
176
0
4
Order By: Relevance
“…re lease large amounts of lac tate in vivo [259][260][261]. Al though stud ies on cell cul tures showed that mi to chon dr ial res pi ra tion is lim ited in sev eral can cer cell lines [262][263][264], in vivo data showed that mi to chon dr ial oxy gen con sump tion is not im paired in tu mors and that ox ida tive glu cose me tab o lism is re quired for tu mor growth [265].…”
Section: Metabolic Differences Between In Vitro and In Vivo Models Ofmentioning
confidence: 99%
“…re lease large amounts of lac tate in vivo [259][260][261]. Al though stud ies on cell cul tures showed that mi to chon dr ial res pi ra tion is lim ited in sev eral can cer cell lines [262][263][264], in vivo data showed that mi to chon dr ial oxy gen con sump tion is not im paired in tu mors and that ox ida tive glu cose me tab o lism is re quired for tu mor growth [265].…”
Section: Metabolic Differences Between In Vitro and In Vivo Models Ofmentioning
confidence: 99%
“…treatment. [17]. Previously, PET was limited to image larger animal models [18] but with improvements in technology and imaging quality, it is increasingly being used on smaller animals.…”
Section: Macroscopic Imaging Techniquesmentioning
confidence: 99%
“…Oesophageal carcinoma is only one of the solid tumours and lymphomas that are studied with 18 F-FDG PET in order to assess tumour response to radiation and chemotherapy treatments, which has been recently summarized [11] in a literature review.…”
mentioning
confidence: 99%